2020
DOI: 10.1515/joc-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing confidentiality protection for ZCZ-OCDMA network using line selection and wavelength conversion based on SOA

Abstract: The physical layer of an optical network is vulnerable towards various types of security threats such as physical infrastructure attacks and eavesdropping, where the security item requires more attention in front of the dramatically grows in network capacity. In this paper, authors propose a comparison in performance of zero correlation zone-Optical Code Division Multiple Access based on different confidentiality mechanisms implemented using existing optical logic components such as line selectors, wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, to enhance channel data rate and increase the number of users, combining of spectral amplitude coding OCDMA (SAC-OCDMA) system with other techniques such as subcarrier multiplexing (SCM) [6] and orthogonal frequency-division multiplexing (OFDM) [7] is required. Also, in the last few years, studies have shown that OCDMA network infrastructure is vulnerable towards several types of security attacks, such as eavesdropping where the safety component needs further safety requirements in the face of dramatic increases in network capacity [8,9]. Nonetheless, OCDMA system performance is limited by a multiple access interference (MAI) impact.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to enhance channel data rate and increase the number of users, combining of spectral amplitude coding OCDMA (SAC-OCDMA) system with other techniques such as subcarrier multiplexing (SCM) [6] and orthogonal frequency-division multiplexing (OFDM) [7] is required. Also, in the last few years, studies have shown that OCDMA network infrastructure is vulnerable towards several types of security attacks, such as eavesdropping where the safety component needs further safety requirements in the face of dramatic increases in network capacity [8,9]. Nonetheless, OCDMA system performance is limited by a multiple access interference (MAI) impact.…”
Section: Introductionmentioning
confidence: 99%